THE SOCIO-ECONOMIC ORIENTATION OF EXCHANGE RATE POLICY IN UKRAINE: CURRENCY BOARD VS OFFICIAL DOLLARIZATION - Savelyev, Yevhen; Kuryliak, Vitalina (Journal of European Economy, 2017)
The article studies the problem of choosing an exchange rate arrangement in Ukraine with priority given to socio-economic living conditions of its population. The concept is based on the assumption that monetary policy should lay the basis for solving the problem of bringing the population’s welfare closer to average European indicators. In Europe, Ukraine ranks among countries with the lowest average wages (173 euros) and pensions (63 euros). In addition, the hryvnia is one of the most undervalued currencies in the world. In view of this, it is necessary to reconsider the country’s exchange rate policy, which is currently based on the free-floating arrangement for the Ukrainian hryvnia. This arrangement will conserve the population’s impoverishment for many years to come, stalling all processes of economic and social development and postponing the country’s Eurointegration plans for an indefinite period of time. Exiting from the economic and welfare crisis should be based on the exchange rate mechanism. For that, it is necessary to revalue the hryvnia’s exchange rate so that to bring within a relatively short period of time the size of wages and pensions (as measured in the currencies of developed countries) close to the level observed in Ukraine one year prior to the beginning of the Russian aggression against Ukraine and the start of the anti-terrorist operation. Further revaluation will be supported by the country’s economic development. In considering exchange rate arrangements, in particular an official dollarization and a currency board arrangement, the authors approach the concusion that it would be feasible to build the country’s exchange rate policy upon the model of the currency board arrangement. However, since the exchange rate is derived from the balance of payments, this task can only be achieved by healthening the country’s finance and using the reserves that are “intuitively obvious”. The majority of them are well-known, while some of them are only gaining in popularity. These include: financing the budget deficit through bond issues; de-shadowing of the economy; de-offshoring; encouraging import substitution; restraining the flight of capital; increasing the transparency of the banking sector; preventing the concealment of foreign currency profits abroad; expanding the spheres for circulation of the hryvnia as domestic currency; special foreign exchange arrangements with «law-abiding» companies; attracting foreign currency cash holdings of the population into the banking sector; expanding the practice of inter-governmental foreign currency swaps; using the nonconvensional instruments of monetary policy by the National Bank to repurchase securities and debt obligations.